p42.3 in Gastric Carcinoma: A Novel Biomarker and Promising Therapeutic Target - Jing, Hui; Wei, Lu-Lu; Huo, Fu-Chun; Ren, Xin; Zheng, Jun-Nian; Pei, Dong-Sheng (Letters in Drug Design & Discovery, 2017)
Objective: To explore the function of p42.3 in gastric carcinoma. Methods: We summarized the intricate regulation of p42.3 in gastric carcinoma from several aspects, namely, the structure features, the expression level, its regulation on cell cycle and EMT, its relationship with miR-29a as well as the optimal feedback circuit involved in. Results: We addressed the complex functions of p42.3 in regulating EMT, migration, invasion, proliferation and the optimal regulation network in GC, as well as the significant up/down-stream signal molecules involved in the pathway. We have also illuminated that miR-29a can inhibit cell proliferation and block the cell cycle, at least in part, via the repression of p42.3. Conclusion: In short, p42.3 might serve as a potential therapeutic target in the treatment of GC.
Keywords: therapeutic target